2015
DOI: 10.1126/scitranslmed.aad3533
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous retroviruses in ALS: A reawakening?

Abstract: New data incriminate the human endogenous retrovirus HERV-K in the pathogenesis of ALS and document that the HERV-K envelope protein can be neurotoxic (Li et al ., this issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Alternatively, there is increasing interest in exogenous factors that might trigger sporadic neurodegeneration. It has been proposed that atypical infections or activation of endogenous retroviruses 143 may be critical. While external environmental factors have been elusive in ALS, there is new interest in the intrinsic environment represented by the microbiome.…”
Section: Looking Forwardmentioning
confidence: 99%
“…Alternatively, there is increasing interest in exogenous factors that might trigger sporadic neurodegeneration. It has been proposed that atypical infections or activation of endogenous retroviruses 143 may be critical. While external environmental factors have been elusive in ALS, there is new interest in the intrinsic environment represented by the microbiome.…”
Section: Looking Forwardmentioning
confidence: 99%
“…The bulk of the genetic determinants of sALS remains elusive, and it is believed that exogenous environmental factors can activate endogenous retroviruses to initiate neurodegenerative changes ( Brown and Al-Chalabi 2015 ). Studies have reported some key features of ALS pathology, such as the involvement of mutated genes encoding RNA-binding proteins including the TARDBP ( Sreedharan et al, 2008 ), fused in sarcoma (FUS) ( Vance et al, 2009 ), and heterogeneous nuclear ribonucleoprotein A1 (HNRNPA1) ( Kim et al, 2013 ).…”
Section: Amyotrophic Lateral Sclerosis Pathologymentioning
confidence: 99%
“…In contrast, it remains unknown whether vertebrate hosts can exploit conserved PCD pathways in eukaryotic pathogens to affect infectious outcomes and maintain barrier immunity. Humans inhale ~10 3 to 10 10 mold conidia (i.e., vegetative spores) daily and, among these, Aspergillus fumigatus represents the most common agent of mold pneumonia worldwide (3). Sterilizing immunity depends on rapid conidial clearance by the respiratory immune system, primarily by neutrophils, macrophages, and monocytes (46), to prevent the formation of multicellular, tissue-invasive hyphae.…”
mentioning
confidence: 99%